Direct fiber laser frequency comb stabilization via single tooth saturated absorption spectroscopy in hollow-core fiber - Wu, Shun (Kansas State University, 2014)
Portable frequency references are crucial for many practical on-site applications, for example, the Global Position System (GPS) navigation, optical communications, and remote sensing. Fiber laser optical frequency combs are a strong candidate for portable reference systems. However, the conventional way of locking the comb repetition rate, frep, to an RF reference leads to large multiplied RF instabilities in the optical frequency domain. By stabilizing a comb directly to an optical reference, the comb stability can potentially be enhanced by four orders of magnitude. The main goal of this thesis is to develop techniques for directly referencing optical frequency combs to optical references toward an all-fiber geometry. A big challenge for direct fiber comb spectroscopy is the low comb power. With an 89 MHz fiber ring laser, we are able to optically amplify a single comb tooth from nW to mW (by a factor of 10^6) by building multiple filtering and amplification stages, while preserving the comb signal-to-noise ratio. This amplified comb tooth is directly stabilized to an optical transition of acetylene at ~ 1539.4 nm via a saturated absorption technique, while the carrier-envelope offset frequency, f0, is locked to an RF reference. The comb stability is studied by comparing to a single wavelength (or CW) reference at 1532.8 nm. Our result shows a short term instability of 6 x10^(-12) at 100 ms gate time, which is over an order of magnitude better than that of a GPS-disciplined Rb clock. This implies that our optically-referenced comb is a suitable candidate for a high precision portable reference. In addition, the direct comb spectroscopy technique we have developed opens many new possibilities in precision spectroscopy for low power, low repetition rate fiber lasers. For single tooth isolation, a novel cross-VIPA (cross-virtually imaged phase array) spectrometer is proposed, with a high spectral resolution of 730 MHz based on our simulations. In addition, the noise dynamics for a free space Cr:forsterite-laser-based frequency comb are explored, to explain the significant f0 linewidth narrowing with knife insertion into the intracavity beam. A theoretical model is used to interpret this f0 narrowing phenomenon, but some unanswered questions still remain.
Keywords: Atomic/molecular physics, Optics; Optics; Physics (0605)